434 Updated clinical data from the melanoma expansion cohort of an ongoing Ph1/1b Study of eganelisib (formerly IPI-549) in combination with nivolumab. (9th November 2020) - Postow, Michael; Sullivan, Ryan; Cohen, Ezra; Gutierrez, Martin; Hong, David; Steuer, Conor; McCarter, Jerry; Zizlsperger, Nora; Kutok, Jeff; O'Connell, Brenda; Roberts, Jennifer; Page, Kara; et al.
Abstract : Background: Eganelisib is a first-in-class, oral, selective PI3K-γ inhibitor. Preclinically, eganelisib reprograms macrophages/myeloid derived suppressor cells (MDSCs) from an immune-suppressive to an immune-activating phenotype and enhances efficacy of checkpoint inhibitors. Efficacy of eganelisib + nivolumab in patients with advanced melanoma resistant to immediate prior anti-PD(L)1 therapy is presented. Methods: IPI-549-01 (NCT02637531 ) evaluates eganelisib in advanced solid tumors, as monotherapy and in combination with nivolumab. The combination expansion dose was eganelisib 40 mg QD PO + nivolumab 240 mg Q2W IV. Combination expansion cohorts include unresectable stage III/IV melanoma patients resistant to immediate prior anti-PD(L)1 therapy. Safety, preliminary clinical activity, PK, and correlative study of blood and tumor biopsy samples were mandated. Results: As of June 1, 2020, 180 patients were treated with eganelisib + nivolumab including 40 with melanoma.The most common (>20% of patients) treatment-emergent adverse events in patients treated with eganelisib + nivolumab (N = 180) were fatigue (34.4%), increased AST (30.0%), increased ALT (26.7%), nausea (25.0%), pyrexia (25.0%), anemia (22.8%), decreased appetite (20.6%), and cough (20.6%). 85 (47.2%) patients experienced at least 1 treatment-emergent serious adverse event (SAE) and 19 (10.6%) had a treatment-related SAE. There was no toxicity unique to the melanoma cohort, and no treatment-related death as assessed by investigators.Preliminary data from the melanoma cohort show that in the efficacy-evaluable population which includes all patients (n=39) who had at least 1 post-baseline response assessment or discontinued treatment due to disease progression, the overall response rate (ORR, ie. CR [complete response] or PR [partial response] per RECIST v1.1) is 7.7%, the disease control rate (DCR, ie. CR, PR, or SD [stable disease]) is 35.9%, and the clinical benefit rate (CBR, ie. CR, PR, or SD of at least 24 weeks from first treatment) is 17.9%, per RECIST v1.1. For patients that received ≤ 2 lines of prior systemic therapy (n=19), the ORR is 15.8%, the DCR is 52.6%, and the CBR is 36.8%. In total, there are 3 patients with PR (duration of response 4–12 months) and 4 with SD > 6 months' treatment duration.Translational data evaluating blood MDSCs, cytokines, and proliferation of previously exhausted CD8 memory T-cells as well as changes in immune cell infiltrates from tumor biopsies will be presented. Conclusions: Eganelisib + nivolumab demonstrates an acceptable safety profile and clinical activity in patients with melanoma who were resistant to immediate prior anti-PD(L)1 therapy. Updated clinical and translational data will be presented. Ethics Approval: The study was approved by WIRB, Study Number 1188591 and IRB Tracking Number: 20180297.